A Novel Approach to Critical Congenital Heart Disease (CCHD) Screening at Moderate Altitude - Erin Lueth; Leilani Russell; Jason Wright; Mark Duster; Mary Kohn; Joshua Miller; Cindy Eller; Marci Sontag; Christopher M. Rausch (MDPI AG, 2016)
The American Academy of Pediatrics (AAP) has endorsed Critical Congenital Heart Disease (CCHD) screening using pulse oximetry nationwide, but, however, acknowledges that altitude may impact failure rates and alternative algorithms may be required at high altitudes. We therefore evaluated a modified screening protocol at an altitude of 6200 feet with the hypothesis that modifications could decrease failure rates. We evaluated 2001 well, newborn infants ≥35 weeks gestation using a modified protocol, which included a lower saturation cutoff for the first screen (85% instead of the AAP recommended 90%) and an oxygen hood intervention between the first two screens. Using our modified screening algorithm, we found a 0.3% failure rate, which was similar to the 0.2% sea-level rate and statistically different from the 1.1% rate identified in a recent study at similar altitude. Had the AAP protocol been used, the failure rate would have increased to 0.8%, which is similar to prior reports near this altitude. Echocardiograms were performed on failing newborns with no CCHD identified. A Birth Defects Registry Database review demonstrated one newborn with CCHD was missed after meeting AAP passing criteria. Overall, this study demonstrates that an alternative algorithm can be implemented at moderate altitude with decreased failure rate and comparable false negative rate.